Democracy and the Politics of Ethnicity and Language in Pakistan During the Bhutto Regime: A Case Study of Balochistan - Changiz Ahmed; Dr. Mohammad Ali; Dr. Adnan Riaz (Journal of Political Studies, 2023)
The article studies the dynamics of ethnic conflict in Balochistan and its relation to the paradigm of democracy in Pakistan during the first elected government in the Bhutto Era. Like many third-world countries, the language controversies in Pakistan have provoked ethnic and political conflicts. Due to disagreements over the national language, the government was unable to develop a constitution for nearly 9 years after independence. Though the dispute was theoretically resolved in 1956, it continues to haunt the state. Although Bhutto was an elected leader, his rule was not immune to ethnic conflicts. Ethnic sentiments garnered attention in Balochistan, triggering confrontations and secessionist tendencies. An insurgency began in Balochistan, causing harm to both the Baloch and the state, and it still exists. The article affirms that in this context, ethnic conflicts have political objectives; the main causes of such conflicts are political, such as under-representation in state institutions, unequal distribution of resources, economic disparities, and, in many cases, the state elite's reluctance to recognise the identity of a particular ethnic minority.